2007
DOI: 10.1073/pnas.0707579104
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of UV-induced ATM/ATR signaling pathways

Abstract: To ensure survival in the face of genomic insult, cells have evolved complex mechanisms to respond to DNA damage, termed the DNA damage checkpoint. The serine/threonine kinases ataxia telangiectasia-mutated (ATM) and ATM and Rad3-related (ATR) activate checkpoint signaling by phosphorylating substrate proteins at SQ/TQ motifs. Although some ATM/ATR substrates (Chk1, p53) have been identified, the lack of a more complete list of substrates limits current understanding of checkpoint pathways. Here, we use immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
251
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(269 citation statements)
references
References 26 publications
10
251
0
8
Order By: Relevance
“…Thus, BAP1 might be involved in the DNA damage response by coordinating H2A ubiquitination. Notably, proteomic studies revealed BAP1 among phosphorylated proteins during DNA damage (15). Nonetheless, the role of BAP1 in the DNA damage response and more generally, the mechanism of tumor suppression exerted by this DUB remain unclear.…”
mentioning
confidence: 99%
“…Thus, BAP1 might be involved in the DNA damage response by coordinating H2A ubiquitination. Notably, proteomic studies revealed BAP1 among phosphorylated proteins during DNA damage (15). Nonetheless, the role of BAP1 in the DNA damage response and more generally, the mechanism of tumor suppression exerted by this DUB remain unclear.…”
mentioning
confidence: 99%
“…O número em parênteses corresponde ao ano de publicação do trabalho e foi adaptada da revisão de Ljungman, 2000. 1 -(Muller 1927); 2 - (Hollaender e Claus, 1936); 3 - (Kelner 1949); 4 - (Watson e Crick, 1953); 5 - (Kanazir e Errera, 1954);6 -(RupertT et al, 1958);7 -(Beukers e Berends, 1960); 8 - (Masters e Pardee, 1962); 9 - (Boyce e Howard-Flanders, 1964;Setlow e Carrier, 1964); 10 - (Holliday 1964); 11 - (Rupp e Howard-Flanders, 1968); 12 -(J E Cleaver 1968); 13 - (Lindahl 1974); 14 - (Witkin 1974);15 -(Wagner e Meselson, 1976); 16 - (Lane e Crawford, 1979;Linzer e Levine, 1979); 17 - (Wilson et al, 1982); 18 - (Mellon et al, 1987);19 -(Kastan et al 1991);20 -(Kastan et al 1992); 21 - (Walworth et al, 1993); 22 - (Fishel et al 1993);23 -(van der Kemp et al 1996); 24 - (Rogakou et al 1998); 25 - (Matsuoka et al, 1998);26 -(Masutani et al 1999); 27 - (Tibbetts et al 1999);28 -(de Boer et al 2002); 29 - (Kannouche et al, , 2004); 30 - (Bartkova et al 2005;Gorgoulis et al 2005); 31 - (Matsuoka et al 2007;Stokes et al 2007); 32 - ( Sugasawa et al 2009) .…”
Section: Luz Uv E Consequências Dos Fotoprodutosunclassified
“…O fosforiloma de ATR revelou 570 alvos de fosforilação após irradiação com luz UV, sendo 498 nunca antes descritos (Stokes et al, 2007). Entre esses alvos, muitos alvos envolvidos com a replicação do DNA (MCMs, RPA, RFC, TopBP1 e DNA polimerases como pol η), reforçando um papel importante no controle de origem de replicação, estabilidade da forquilha e recuperação da replicação.…”
Section: Atr: O Bombeiro Controlando O Fogo No Dnaunclassified
“…Posttranslational modifications are of great importance during the cellular DNA damage response (DDR). Indeed, different protein kinases responsible for phosphorylating a plethora of proteins are involved (1,2). Furthermore, tremendous work during the last 2 decades showed the crucial role of protein ubiquitination in the cellular DDR (3).…”
Section: Introductionmentioning
confidence: 99%